رؤية تحليلية في بحوث تفاعل المعالجات "بيئات التعلم الافتراضية"- الاستعدادات "أساليب التعلم" - عطية، يسري مصطفى السيد (جامعة سوهاج - كلية التربية, 2021)
توالت خلال العقود الثلاثة الأخيرة (1990-2020م) البحوث في علم تكنولوجيا التعليم التي اهتمت باستقصاء آثار التفاعل بين المعالجات التدريسية التي تعتمد على مستحدثات تكنولوجيا التعليم واستعدادات المتعلمين في مختلف المقررات والمراحل الدراسية، ومع ظهور بيئات التعلم التفاعلية والافتراضية توجه الباحثون لدراسة مدى وجود تفاعل بين سمات ومكونات هذه البيئات، وبين استعدادات المتعلمين وأساليبهم الإدراكية وأنماط تعلمهم المفضلة. وقد اهتمت الدراسة بتناول ميزات بيئات التعلم الافتراضية، والأساليب المفضلة في تعلم الطلاب، مع إلقاء الضوء على بحوث التفاعل بين المعالجات والاستعدادات وتطورها منهجيا، تمهيدا لطرح رؤية تقويمية لبحوث التفاعل بين المعالجات والاستعدادات تقوم على عدة دراسات عربية وأجنبية استخدمت منهجية التحليل البعدي. تعرض هذه الدراسة واقع نماذج/ قوائم تحديد أساليب التعلم وتعددها وتباين النظريات التي قامت عليها، وانتهت بعرض خلاصة ركزت على توصيات ضرورية للباحثين عند الشروع في إعداد أبحاث تفاعل المعالجات والاستعدادات في مجال تكنولوجيا التعليم.
During the last three decades (1990-2020), researches in the science of educational technology continued to investigate the interaction effects between teaching treatments that depend on educational technology innovations and the aptitudes of learners in different courses and study levels. The emergence of interactive and virtual learning environments prompted researchers to study the existent extent of interaction between the features and components of these environments, and the aptitudes of learners, their perceptual methods and their preferred learning styles. The study focuses on the virtual learning environments' features, and the preferred methods of student learning, sheds light on researches of interaction between treatments and aptitudes, and their methodological development, and provides an evaluation view for interaction researches between treatments and aptitudes based on several Arab and overseas studies that used the dimensional analysis methodology. This study presents the reality of models/ lists of determining learning styles, their plurality, and the variation of theories on which they are based. It ends by conclusion focuses on necessary recommendations for researchers when conducting interaction researches between treatments and aptitudes in educational technology field.
Keywords: تكنولوجيا التعليم -- بيئات التعلم الافتراضية -- أساليب التعلم -- التعليم الإلكتروني